Analysis of factors affecting immune recovery and initial response to tetanus after DTaP vaccination in pediatric allogeneic HSCT patients. (22nd September 2014) - Boles, Erin E.; Chiuzan, Codruta; Ragucci, Dominic; Hudspeth, Michelle P.
Abstract Transfer of donor immunity after allo‐HSCT is limited, requiring re‐vaccination after HSCT. The CDC 2009 guidelines introduced earlier vaccination post‐HSCT with a uniform vaccination strategy. This study objective was to describe predictors of immune recovery and initial response to tetanus after DTaP vaccination post‐HSCT. We conducted a retrospective chart review of pediatric allo‐HSCT patients transplanted between July 1, 2007–June 30, 2012 who survived >1 yr without relapse (N = 27). Response to tetanus one month after the initial dose of DTaP was defined as a ≥4 fold increase in tetanus titers ≥1 month after vaccination. Wilcoxon rank‐sum exact test and Kruskall–Wallis tests were used to analyze CD4, CD8, and CD19 counts. Exact conditional logistic regression was utilized to analyze initial tetanus vaccination response. A statistically significant increase in median CD4, CD8, and CD19 counts occurred from six to 12 months post‐HSCT (p ≤ 0.0001, 0.005, 0.004). Only 36% of patients had initial tetanus vaccination response at first attempt post‐HSCT. None of the variables tested were statistically significant in predicting initial tetanus response to vaccination. There was no association between predictors of immune recovery or transplant variables and initial tetanus response. A uniform vaccination strategy is unlikely to provide protective antibodies for many post‐HSCT patients and should be evaluated in larger studies.